Investigation of the Effect of (Urea + Ammonia + Calcium Oxalate) Mordant Mixture on the Dyeing of Wool, Feathered-Leather and Cotton - Onal, Adem; Kahveci, Ismail; Soylak, Mustafa (Asian Journal of Chemistry, 2010)
A new development was carried out in the dyeing of wool, feathered-leather and cotton using the root of common madder (Rubia tinctorum L.). The mordant effect of the (H2N—CO—NH2 + NH3 + CaC2O4 mixture was widely investigated using a pre-mordanting method. Samples were mordanted in each chemical and combination of urea, ammonia, calcium oxalate,;urea + ammonia, urea + calcium oxalate, ammonia + calcium oxalate and urea + ammonia + calcium oxalate. Selected transition element salts such as Cu(NO3)2·3H2O, MnSO4·H2O, Ni(CH3COO)2·4H2O, Al(NO3)3·9H2O, SnCl2·2H2O, Fe(NO3)2·9H2O, Zn(NO3)2·6H2O were used as second mordant agents after every combination. Dyeing conditions and colour codes and fastness were determined to obtain repeatable processes. High fastness colours were obtained using the triplex mixture of (urea + ammonia + calcium oxalate). In addition, resolution energies of complexes were calculated using the HyperChem computer programme.